Islamic Theology And Rasionalism: Analisis Pemikiran Sutan Takdir Alisyahbana - Kohar, Abdul (Tribakti: Jurnal Pemikiran Keislaman, 2020)
This paper explores the thoughts of Sutan Takdir Alisyahbana (STA). STA is referred to as a cultural practitioner, because it discusses more the cultures that enter Indonesia, such as Indian, Hindu, Buddhist, Islamic and native Indonesian culture, even it also discusses western culture. He also wrote a lot such as poetry, novels, philosophy books and he was among the first to make Indonesian terms, so he was called a writer. This research is a type of library research (library research) by presenting qualitative-interpretative data. The purpose of this study is to reveal the fact that the religion of Islam in Indonesia is a religion that does not dichotomize between the reality supported by invoices and spiritual reality because Islam today is deeply engrossed in the history of the development of Islam in the time of the Prophet Muhammad, also today Islam is shackled with religious myths, so as to be able to resolve Islam in Indonesia, it cannot develop and is anti-Western rationality. STA thinking is rooted in the humanist understanding that developed in Europe from the Renaissance to the rise of new-positivism. Its humanism is built on human liberation from the shackles of mythology and religion.